(untitled) (Research, Society and Development, 2020)
Objective: To discuss the nursing interventions applicable during post-discharge telephone follow-up for patients with onco-hematological disease. Method: Exploratory research with a mixed approach, a single case study type. The sample consisted of 21 participants, eight from the intervention group and 13 from the control group. Nursing interventions were applied according to the NIC standard (Nursing Intervention Classification, 2010) for “Monitoring by phone” to the intervention group. Simple descriptive statistical analysis was performed. Results: the nursing interventions 100% applied were: actively listening, counseling, supervision, skin supervision, nutrition control, protection against infection; the 75%: infection control, medication control and bleeding precautions; 50%: bathing, control of the environment and reduction of gastrointestinal bleeding. Conclusion: It is a technology that can be combined with nursing care for onco-hematological patients, as it favors the maintenance of the patient’s bond with the nurse, allows assistance to clarify doubts after discharge, in addition to encouraging adherence to treatment and management of self-care.